Total synthesis of the putative structure of xylarinol B - More, Atul A.; Ramana, Chepuri V. (Chemistry-An Asian Journal, 2014)
The total synthesis of the putative structure of xylarinolB is described and the need to revise its structure is demonstrated. The central benzoxepine skeleton was constructed by employing a cobalt-mediated bimolecular [2+2+2] Reppe-Vollhardt alkyne cycloaddition reaction.
Keywords: Chiral pool; cobalt; Natural products; structure elucidation; Total synthesis

Target cum flexibility: synthesis of indolo[1,2-b]isoquinoline derivatives via cobalt-catalyzed [2+2+2] cyclotrimerization - Swami, Anuradha; Ramana, Chepuri V. (Synlett, 2015)
A modular approach for the synthesis of small molecules having the unnatural 6,11-dihydroindolo[1,2-b]isoquinoline tetracyclic core has been documented. An acid-catalyzed Friedel-Crafts-type C2-alkylation of N-propargyl indole with a suitably activated alkynol has been used to prepare the key indole-derived diynes. The cobalt-catalyzed [2+2+2] cyclotrimerization of these diynes has been studied with various internal/terminal alkynes and with nitriles.
Keywords: 2-b]-isoquinoline; cobalt; Indole; indolo[1; Pyridine; [2+2+2] cyclotrimerization